Vasoconstrictive responses by the carotid and auricular arteries in goats to ergot alkaloid exposure1 - Aiken, Glen E.; Flythe, Michael D. (Frontiers in Chemistry, 2014)
A fungal endophyte (Neotyphodium coenophialum) infects most plants of ‘Kentucky 31’ tall fescue (Lolium arundinaceum) and produces ergot alkaloids that cause persistent constriction of the vascular system in grazing livestock. Consequently, animals undergoing this toxicosis cannot regulate core body temperature and are vulnerable to heat and cold stresses. An experiment was conducted to determine if the caudal and auricular arteries in goats (Capra aegagrus hircus) vasoconstrict in response to ergot alkaloids. Seven, rumen fistulated goats were fed ad libitum orchardgrass (Dactylis glomeratia) hay and ruminally infused with endophtye-free seed (E-) for a 7-day adjustment period. Two periods followed with E- and endophyte-infected (E+) seed being randomly assigned to the 2 goat groups in period 1 and then switching treatments between groups in period 2. Infused E+ and E- seed were in equal proportions to the hay such that concentrations of ergovaline and ergovalanine were 0.80 µg per g dry matter for the E+ treatment. Cross-sections of both arteries were imaged using Doppler ultrasonography on days 0, 2, 4, 6, 8, and 12 in period 1 and on days 0, 1, 2, 3, 6, 7, and 9 in period 2. Differences from average baseline areas were used to determine presence or absence of alkaloid-induced vasoconstriction. Carotid arteries initiated constriction on imaging day 2 in both periods, and auricular arteries initiated constriction on imaging day 2 in period 1 and on day 6 in period 2. Luminal areas of the carotid arteries in E+ goats were 46% less than baseline areas in both periods after vasoconstriction occurred, whereas auricular arteries in E+ goats were 52% less than baseline areas in period 1 and 38% in period 2. Both arteries in E+ goats in period 1 relaxed relative to baseline areas by imaging day 2 after they were switched to the E- treatment. Results indicated that goats can vasoconstrict when exposed to ergot alkaloids that could disrupt their thermoregulation.